A farming system approach to support policies for food security under climate change in developing countries: the case of Mozambique - Abbas, Miriam Abdul Gani (2022)
Doutoramento em Estudos de Desenvolvimento / Instituto Superior de Agronomia / ISEG / ICS / IGOT - Universidade de Lisboa